If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + 13) = 25 Reorder the terms: 5(13 + 2x) = 25 (13 * 5 + 2x * 5) = 25 (65 + 10x) = 25 Solving 65 + 10x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-65' to each side of the equation. 65 + -65 + 10x = 25 + -65 Combine like terms: 65 + -65 = 0 0 + 10x = 25 + -65 10x = 25 + -65 Combine like terms: 25 + -65 = -40 10x = -40 Divide each side by '10'. x = -4 Simplifying x = -4
| -5(0-6)=0 | | (x-3)/×=96.5 | | x+x+7018.75=280612.06 | | 36-X=52(3) | | 2p^2+9p+10=0 | | 3((3x^2)+(y^2))dx-(2xy)dy=0 | | x+x-7=280612.06 | | (x-3)/×96.5 | | (-3x+2i)(x-6i)=0 | | -3y=9x-7 | | 1.42857x+10=0.375x+3 | | x+10=2000 | | a^3-7a+10bya-2= | | x+x+7=280000 | | 11+4x=-5x+7 | | 9(2x+1)=3(5x-3) | | 5y+12=2 | | 13+(12)-3=-2 | | 12(23+13)=12(45-1) | | 17-(4-6y)+4=42 | | 24x+5=20x-13 | | sin(11x)*sin(x)=cos(10x) | | 12(23+13)= | | 3(x-1)-(x-2)=3(x-4) | | 16X-2(3x+1)=10 | | 20b^3+15b^2=0 | | 5x+7=-1-3x | | 5(2x+1)-12x=19 | | x+sqrt(5)+4x=17-3x | | 3(2-z)=0.4(2z-20) | | 0=-0.375x+3 | | 6y+8=8y-2 |